Representasi Pengambilan Keputusan Oleh Tokoh Minke di Tengah Penindasan Kolonial pada Film Bumi Manusia - Yuandina, Radhika; Amaliyah, Amaliyah; Dimisqiyani, Erindah; Amalia, Rizky (CV. Pusdikra Mitra Jaya, 2025)
Decision-making is crucial for both individuals and organizations because the quality of decisions made today will determine the direction and sustainability of the future. In educational and social contexts, sound decisions play a crucial role in realizing justice, equality, and progress at the institutional and societal levels. This article focuses on the analytical decision-making style demonstrated by Minke in the film Bumi Manusia (2019), examining the main character's thought processes and actions when facing complex situations. This research uses a qualitative descriptive method through film observation, by closely observing scenes, dialogues, and interactions between characters, then analyzing them based on analytical decision-making theory. The results reveal that Minke consistently demonstrates an analytical decision-making style in several key events, such as choosing an intellectual path through writing, supporting Nyai Ontosoroh's struggle, continuing his education despite facing discrimination, rejecting offers from colonial officials, and maintaining loyalty to Annelies. These decisions reflect a structured mindset, a long-term orientation, moral courage, and integrity grounded in humanitarian values. These findings suggest that an analytical style is an effective strategy in facing social and political challenges because it combines analytical acumen with a moral foundation. Thus, this research contributes to enriching insight into the dynamics of decision-making and opens up opportunities for further studies on other decision-making styles in the representation of film as a popular medium.